2009
DOI: 10.1016/j.jvs.2008.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention for thoracic outlet syndrome improves patient's quality of life

Abstract: The use of the SF-12 and DASH instruments in patients with TOS demonstrated significant improvement in patients postoperatively. Venous TOS patients typically improved both physical and mental scores in shorter periods of time than their neurogenic counterparts. Neurogenic and venous TOS patients returned to full-time work/activity within the same length of time postoperatively. However, neurogenic patients required more secondary interventions. We conclude that in appropriately selected patients with either n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
84
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 25 publications
7
84
0
1
Order By: Relevance
“…1,[9][10][11] This QD survey for disorders of the upper extremities has been extensively validated in orthopedic and hand surgery literature and has been used in TOS outcomes reports. 12 The QD instrument uses 11 items to objectively measure physical function and symptoms in people with any or multiple musculoskeletal disorders of the upper limb. Scores range from 0 points (asymptomatic) to 100 (totally incapacitated).…”
Section: Methodsmentioning
confidence: 99%
“…1,[9][10][11] This QD survey for disorders of the upper extremities has been extensively validated in orthopedic and hand surgery literature and has been used in TOS outcomes reports. 12 The QD instrument uses 11 items to objectively measure physical function and symptoms in people with any or multiple musculoskeletal disorders of the upper limb. Scores range from 0 points (asymptomatic) to 100 (totally incapacitated).…”
Section: Methodsmentioning
confidence: 99%
“…We have used the DASH questionnaire which has been developed by the American Academy of Orthopaedic Surgeons (http:// www.dash.iwh.on.ca/) as a measure of the functional status and disability after surgery [13]. Several studies validated the questionnaire as an objective tool in evaluating post operative outcomes [7].…”
Section: Methodsmentioning
confidence: 99%
“…It contains 30 questions, where by scoring each item on the scale between 1 (no difficulty) to 5 (unable), patients describe the severity of their symptoms [7]. The overall score ranges from 0 points (asymptomatic patient) to 100 points (severe symptoms) [7,13].…”
Section: Methodsmentioning
confidence: 99%
“…All patients were also examined for symptoms and signs of neurogenic TOS, including completion of the Disabilities of the Arm, Shoulder and Hand (DASH) survey instrument. [7][8][9][10][11] Plain chest radiographs (CXR), magnetic resonance angiography (MRA), and computed tomography angiography (CTA) studies were performed as indicated by clinical circumstances, but were not specifically obtained for this study. Preoperative imaging studies were reviewed for the presence of osseous abnormalities, such as cervical ribs and overt first rib fractures, but were not specifically assessed for the presence of CC or OD.…”
Section: Methodsmentioning
confidence: 99%